Why Do We Use Pesticides? - Frederick M. Fishel (EDIS)
This guide explains the benefits of pesticide use and why they are important in our society. Examples are provided to illustrate the importance of pesticides and the living conditions that are not possible without their use. This document is PI-103, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.